Single Dose Gonadotropin-Releasing Hormone Agonist Luteal Support in Fresh Embryo Transfer: Variation in Timing, Type, and Dosage - Abu, Muhammad Azrai; Alexander, Jojinah Vindah; Abdul Karim, Abdul Kadir; Ahmad, Mohd Faizal; Omar, Mohd Hashim (Frontiers in Medicine, 2022)
Objectives: To evaluate the effects of the addition of single-dose GnRH agonist to the routine progestogens use for luteal phase support on IVF outcome as compared to progestogens only. Methods: This is a retrospective case-control study on selected patients who underwent IVF treatment with fresh embryo transfer (ET) under Medically Assisted Conception Unit, University Kebangsaan Malaysia Medical Centre for the period of June 2015-June 2018. A higher dose of 0.2 mg subcutaneous Decapeptyl was administered 2 days before fresh ET concurrent with routine progestogen support. Patients with different luteal phase regimes, frozen embryo transfer, and medical records with missing data were excluded. Their medical records were reviewed, and data were analyzed. The pregnancy outcomes measured included biochemical pregnancy rates, clinical pregnancy rates, live birth rates, and miscarriage rates. Results: A total of 786 patients were analyzed. 444 patients were given luteal phase support with progestogens and GnRH agonist, whereas 342 patients served as control were given progestogens only. The study group showed a higher biochemical pregnancy rate (47.7% vs 44.4%,), clinical pregnancy rate (25.7% vs 23.4%), and live birth rate (24.3% vs 22.2%) respectively but not statistically significant. The rate of miscarriage among the study group was lower (4.5% vs 9.4%) compared to the progestogen group alone. Nonetheless, the OHSS rate was slightly increased in the study group (4.5% vs 3.5%) despite using a mild stimulation protocol. Conclusions: New regime of GnRH agonist luteal support in addition to the standard progestogen support was found to be beneficial in overall IVF outcome.